Efek Ekstrak Bunga Melati (Jasminum Sambac) dengan Metode Elektrik terhadap Efek Knockdown pada Nyamuk Aedes Aegypti Stadium Dewasa - Rizky Noni Amalia; Anung Putri Illahika; Aida Musyarrofah; Fathiyah Safithri (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
Abstract. Dengue Hemorrhagic Fever (DHF) is caused by the Dengue virus (DENV) which is transmitted by mosquitoes. One of the factors that cause high number of dengue infections in Indonesia is due to poor vector management. Chemical-based insecticides used to control mosquitos can cause human health problems and mosquito resistance. Jasmine flower (Jasminum sambac) can be used as an alternative because it contains flavonoids, alkaloids, saponins, and tannins that can act as natural insecticides. Objective: Proving the effect of jasmine flower extract (Jasminum sambac) with the electric method has a knockdown effect on adult stage Aedes aegypti mosquitoes. Method: True Experimental Post Test Only Control Group Design. In each test group, 20 adult Aedes aegypti were used with four replications. In this study, the test group consisted of malathion as positive control, aquades as negative control, and jasmine flower extract (Jasminum sambac) at concentrations of 5%, 10%, 15%, 20%, and 25%. Data was analyzed using Kruskal Wallis test, Post Hoc Mann Whitney test, Spearman correlation test and Probit test. Results and Discussion: Kruskal Wallis test obtained a significance value (P) <0.05. Post hoc mann whitney test showed knockdown effect at concentrations of 15%, 20% and 25%. The results of the Spearman correlation test (P = 0.019 and R = 0.440) showed a sufficient correlation between the concentration of jasmine flower extract and the knockdown effect. LC50 was obtained by probit test at a concentration of 12.839%. The results showed that the content of jasmine flower extract had an insecticidal effect with the electric method. Conclusion: Jasmine flower extract (Jasminum sambac) applied using the electric method has a knockdown effect on adult Aedes aegypti at concentrations of 15%, 20% and 25%.